The Role of Elective English for Specific Purposes (ESP) in Preparing Beauty Vocational Students for the World of Work: A Qualitative Case Study - Maya Ulyani (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
This study aims to examine the role of elective English for Specific Purposes (ESP) in preparing beauty vocational students for participation in the global workforce. Using a qualitative descriptive approach, the research was conducted at SMKN 2 Selong, East Lombok, and involved 15 participants comprising students, teachers, and a curriculum coordinator. Data was gathered through interviews, classroom observations, and document analysis, and then analyzed thematically to identify patterns in instructional practices and stakeholder perceptions. The findings indicate that integrating beauty-specific English content into ESP instruction enhances students’ communicative competence, motivation, and confidence in professional contexts. The use of authentic materials such as product catalogs, salon manuals, and customer-service simulations was found to increase classroom engagement and support practical language use. However, the study also identified key challenges, including limited instructional resources, inadequate teacher training, and the lack of performance-based assessment. The study implies that ESP is essential for bridging language education and industry needs in vocational settings. To maximize its effectiveness, stronger institutional support, targeted teacher development, and collaboration with the beauty industry are recommended.